THE TOTAL COMMUNICATION FOR HEARING-IMPAIRED STUDENTS IN LEARNING ENGLISH - Mohammad - Halili; Mahbub Arham Arrozy (STBA LIA - Jakarta, 2021)
This study aims to discuss the use of Total Communication (TC, henceforth), the combinations of communication modes, and the reasons for using TC for hearing-impaired (HI) students of English class at SLB PGRI Kamal. Teaching English to them is believed to require more strategic approaches especially when compared to students who do not have any hearing issues. The data are from four HI students at SLB PGRI Kamal and their English teacher. In collecting the data, observation, note taking and recording were used as the instruments in which during taking note and observation, the researchers used phone recorder and phone camera to anticipate the data from lost and for further analysis. The results show that there are seven communication modes that were used. Those are lip-reading, sign language, images, writing, Indonesian Alphabetic Symbol System (IAS), finger spelling, and speech. Those modes are combined depending on the needs of the users (both English teacher and HI students). Therefore, the researcher found six combinations of modes in TC. Moreover, the researchers found five reasons for using TC for HI students in the English classroom at SLB PGRI Kamal. It is because of its flexibility and effectiveness in communication. Futhermore, TC gives chances to HI students to learn to speak, write and read in English, and allow the HI students to make English sounds and identify them